1994
DOI: 10.1007/bf01957008
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of recurrent thrombotic thrombocytopenic purpura with plasmapheresis and vincristine

Abstract: An adolescent girl with severe thrombotic thrombocytopenic purpura (TTP) remained in a critical condition after 3 weeks of combined treatment with antiplatelet drugs, plasma infusions and plasma exchange. The introduction of vincristine resulted in gradual improvement and eventual complete remission which lasted for 2 years. When she relapsed, immediate improvement was observed with the combined treatment of plasmapheresis and vincristine. She has now been in complete remission again for 10 months. It is sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…1 Kinetics of platelet count and serum LDH value in a responding patient several reports on the use of VCR for TTP have appeared in the literature. However, most of these described very small series or anecdotal patients; in addition, the schedule of VCR adopted in the different studies varied considerably [3,9,12]. The two largest series were published by Bobbio-Pallavicini et al in 1994 [1] and Mazzel et al in 1998 [4].…”
Section: Discussionmentioning
confidence: 99%
“…1 Kinetics of platelet count and serum LDH value in a responding patient several reports on the use of VCR for TTP have appeared in the literature. However, most of these described very small series or anecdotal patients; in addition, the schedule of VCR adopted in the different studies varied considerably [3,9,12]. The two largest series were published by Bobbio-Pallavicini et al in 1994 [1] and Mazzel et al in 1998 [4].…”
Section: Discussionmentioning
confidence: 99%
“…In another case, oral cyclophosphamide resulted in a complete response in two patients with refractory TTP [16]. Van Gool et al [40] suggested the use of plasmapheresis plus vincristine in recurrent disease and for initial treatment. Despite these partially successful regimens a more rational approach and a better understanding of the pathogenesis was desirable.…”
Section: Discussionmentioning
confidence: 99%
“…The resemblance of TTP to disorders in which vasculitis is prominent, e.g., systemic lupus erythematosus, prompted the use of cytotoxic agents such as vincristine sulfate in TTP patients. With vincristine, the results in TTP patients have been favorable in some case reports [13,23,25,27]. In other studies the benefit of vincristine was not confirmed [5] (see also Table 1).…”
Section: Introductionmentioning
confidence: 97%